Multifaceted potential applicability of hydrotalcite-type anionic clays from green chemistry to environmental sustainability. (November 2022) - Kumari, Sonika; Sharma, Ajay; Kumar, Satish; Thakur, Abhinay; Thakur, Ramesh; Bhatia, Shashi Kant; Sharma, Anil Kumar
Abstract: Hydrotalcite-like anionic clays (HTs) also known as Layered double hydroxides (LDHs) have been developed as multifunctional materials in numerous applications related to catalysis, adsorption, and ion-exchange processes. These materials constitute an important class of ionic lamellar solid clays of Brucite-like structure which comprise of consecutive layers of divalent and trivalent metal cations with charge balancing anions and water molecules in interlayer space. These materials have received increasing attention in research due to their interesting properties namely layered structure, ease of preparation, flexible tunability, ability to intercalate different types of anions, electronic properties, high thermal stability, high biocompatibility, and easy biodegradation. Moreover, HTs/LDHs have unique tailorable and tuneable characteristics such as both acidic and basic sites, anion exchange capability, surface area, basal spacing, memory effect, and also exhibit high exchange capacities, which makes them versatile materials for a wide range of applications and extended their horizons to diverse areas of science and technology. This study enlightens the various rational researches related to the synthetic methods and features focusing on synthesis and/or fabrication with other hybrids and their applications. The diverse applications (namely catalyst, adsorbent to toxic chemicals, agrochemicals management, non-toxic flame retardants, and recycling of plastics) of these multifunctional materials related to a clean and sustainable environment were also summarized. Graphical abstract: Image 1 Highlights: Hydrotalcite-like anionic clays are multifunctional mineral materials. Have properties like flexible tunability, thermal stability, and biodegradability. Easy to synthesize and fabricate. Used as catalyst for organic synthesis and adsorbent for contaminant removal. HTs/LDHs are used as carriers for the controlled release of agrochemicals.